IteRates: An R Package for Implementing a Parametric Rate Comparison on Phylogenetic Trees. (January 2014) - Fordyce, James A.; Shah, Premal; Fitzpatrick, Benjamin M.
Patterns of diversification rate variation detected in phylogenetic hypotheses are frequently used to infer historical, ecological, and evolutionary processes. The parametric rate comparison (PRC) is a method for detecting rate variation in trees that models branch lengths as random variables drawn from familiar statistical distributions. iteRates is a library of functions for the R statistical computing environment for implementing PRC on phylogenetic trees. Here, we describe some of the functions in iteRates for subtree identification, tree manipulation, applying the PRC and K -clades PRC analyses, and conducting a whole-tree randomization test.